Poisonous Plants Phenology: A Case Study of Belpahari Forest Region of Jhargram District, West Bengal - Mahapatra, Bingshati Singha; Jana, Susanta; Mallick, Shyamal Kanti (Indian Forester, 2025)
The present study deals with the taxonomic exploration and phenology of some poisonous plants found in the different forest patches of Belpahari forest region of Jhargram District, West Bengal. Phenology is the morphological expression of physiological activities of the plants. Plant phenological study has great significance because it not only provides knowledge about plant pattern but also provides the idea on the effects of environmental and selective pressure on flowering and fruiting behaviour. The phenological study of selected poisonous plants depends on the observation, interpretation and recording of the timing of their life history events. During this time different phenophases such as vegetative growth, flowering and fruiting time, seed germination, ripening of fruits and leaf senescence were observed timely in every month. Among six plants maximum plant species showed germination during June to July. Maximum flowering and fruiting times are September and October to December.